Replacement of Legal Guardianship with Judicial Guardianship Theoretical Perspectives and Practical Implications - Farohi, Ahmad Farohi Mubarok; Nizar, Muchamad Coirun Nizar (ADHKI: JOURNAL OF ISLAMIC FAMILY LAW, 2024)
Problem statement: The absence of a guardian at a wedding can result in the marriage contract not being executed. One of the causes is masafatul qashri, wherein a guardian is unable to attend his daughter's wedding ceremony due to long distance. Objective: The purpose of this study is to elucidate the positive legal provisions in Indonesia regarding the replacement of the lineage guardian with a guardian appointed by the court due to masafatul qashri, as well as the criteria for masafatul qashri that permit the transfer of authority from the lineage guardian to the court-appointed guardian, from the perspective of scholars from the four schools of thought. Methods: This research employs a library-based methodology using a comparative approach, with data collection through documentation of texts authored by scholars from the four schools of thought and positive law in Indonesia. Results: The results of this study reveal differences in the replacement of the biological guardian with a judicial guardian due to masafatul qashri as outlined in the Regulation of the Minister of Religion of the Republic of Indonesia (PMA RI) No. 20 of 2019, the Compilation of Islamic Law (KHI), and the views of madhhab scholars. In the PMA, the issue no longer pertains to the guardian appointed by the court but instead utilises the procedure of delegating guardianship, thereby maintaining the recognition of the biological guardian. Conversely, the KHI does not address the issue of masafatul qashri. Prior to 2018, the replacement of the biological guardian with a judicial guardian due to masafatul qashri was still applicable based on PMA No. 30 of 2005, which was subsequently revised by PMA No. 11 of 2007 and again by PMA No. 19 of 2018. Scholars from the various schools of thought also express differing opinions; the Shafi’i and Maliki schools assert that in cases of masafatul qashri, the one entitled to act as guardian is the ruler (sultan), while according to the Hanafi and Hambali schools, the rightful guardian is the wali ab’ad. Conclusion: This study illuminates contemporary societal challenges related to marriage guardianship, one of which is the necessity of a guardian as a primary requirement for the validity of a marriage.